1993
DOI: 10.1006/cbir.1993.1003
|View full text |Cite
|
Sign up to set email alerts
|

Partial activation of surf clam oocytes by hypertonic treatment.

Abstract: In prophase I‐arrested surf clam oocytes, fertilization is the normal trigger for resumption of meiosis, first evidenced by germinal vesicle breakdown (GVBD). Various artificial agents are able to induce GVBD and most of them require the presence of external Ca2+ to be efficient. One exception to this rule is the reported possibility of inducing GVBD by an hypertonic treatment, using high concentrations of glycerol, in the complete absence of external Ca2+. We have investigated the processes underling glycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…One notable exception to this rule was reportqd by Dessev and Goldman (1990) who showed that hypertonic treatment led to GVBD in Spisula oocytes, in the absence of external caZ+. We have confirmed this observation but showed that the timing of GVBD, upon hypertonic treatment, was much slower than normal and that oocytes would not proceed further to polar body extrusion nor to the alignment of chromosomes in a normal metaphase, suggesting an absent or deficient meiotic spindle (Coutu et al, 1993). This intriguing phenomenon may be interpreted in different ways, all of which might not be relevant to the physiological process.…”
Section: Alternative Means Of Activating Spisula Oocytes Besides a Fsupporting
confidence: 60%
“…One notable exception to this rule was reportqd by Dessev and Goldman (1990) who showed that hypertonic treatment led to GVBD in Spisula oocytes, in the absence of external caZ+. We have confirmed this observation but showed that the timing of GVBD, upon hypertonic treatment, was much slower than normal and that oocytes would not proceed further to polar body extrusion nor to the alignment of chromosomes in a normal metaphase, suggesting an absent or deficient meiotic spindle (Coutu et al, 1993). This intriguing phenomenon may be interpreted in different ways, all of which might not be relevant to the physiological process.…”
Section: Alternative Means Of Activating Spisula Oocytes Besides a Fsupporting
confidence: 60%